Excessive activation of mTOR in postnatally-generated granule cells is sufficient to cause epilepsy - Pun, Raymund Y.K. (2012)
The dentate gyrus is hypothesized to function as a “gate”, limiting the flow of excitation through the hippocampus. During epileptogenesis, adult-generated granule cells (DGC) form aberrant neuronal connections with neighboring DGC, disrupting the dentate gate. Hyperactivation of the mTOR signaling pathway is implicated in driving this aberrant circuit formation. While the presence of abnormal DGC in epilepsy has been known for decades, direct evidence linking abnormal DGC to seizures has been lacking. Here, we isolate the effects of abnormal DGC using a transgenic mouse model to selectively delete PTEN from postnatally-generated DGC. PTEN deletion led to hyperactivation of the mTOR pathway, producing abnormal DGC morphologically similar to those in epilepsy. Strikingly, animals in which PTEN was deleted from ≥9% of the DGC population developed spontaneous seizures in about four weeks, confirming that abnormal DGC – which are present in both animals and humans with epilepsy – are capable of causing the disease.